2020
DOI: 10.1002/pat.5159
|View full text |Cite
|
Sign up to set email alerts
|

Effect of electric stimulus on human adipose‐derived mesenchymal stem cells cultured in 3D‐printed scaffolds

Abstract: Electrical stimulation has shown great potential for nerve regeneration processes. This makes it attractive to use electrically active materials in the neural scaffold. In this paper, bismuth ferrite (BFO) nanoparticles were synthesized via co‐precipitation method and incorporated to 10 wt% polylactic acid (PLA) in chloroform to obtain 3D‐printed PLA/BFO biocomposites. The crystallinity of BFO nanoparticles was confirmed by XRD, and we studied its chemical structure with FTIR, as well as the mechanical propert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…To investigate the interaction of chemical and molecular structure in produced CHT scaffolds, FT-IR analysis was carried out on the four groups. These scaffolds that were containing different concentrations of BFO, present the following specific vibrations: the characteristic absorption bands at 1565 𝑐𝑚 −1 , 1375 𝑐𝑚 -1 852 𝑐𝑚 -1 , which are associated with familiar vibrations for C≡CH, N-H and saccharide [14]. The distinctive peak is in the absorption band at 815 cm −1 in the spectrum for all experimental groups.…”
Section: Resultsmentioning
confidence: 92%
“…To investigate the interaction of chemical and molecular structure in produced CHT scaffolds, FT-IR analysis was carried out on the four groups. These scaffolds that were containing different concentrations of BFO, present the following specific vibrations: the characteristic absorption bands at 1565 𝑐𝑚 −1 , 1375 𝑐𝑚 -1 852 𝑐𝑚 -1 , which are associated with familiar vibrations for C≡CH, N-H and saccharide [14]. The distinctive peak is in the absorption band at 815 cm −1 in the spectrum for all experimental groups.…”
Section: Resultsmentioning
confidence: 92%
“…In addition, it was observed that 13 %% PVA/ (0.075)% BFO_RIF scaffolds (45.54 %) had lower strain at break compared to 13 % PVA/(0.075)% BFO_AMX scaffolds (53.24 %). The low interfacial adhesion of PVA and BFO particles is due to poor bonding between PVA and BFO particles [13] . As a result, the addition of BFO to the scaffolds decreased strain at break values since the interaction of PVA and BFO was less.…”
Section: Resultsmentioning
confidence: 99%
“…The low interfacial adhesion of PVA and BFO particles is due to poor bonding between PVA and BFO particles. [13] As a result, the addition of BFO to the scaffolds decreased strain at break values since the interaction of PVA and BFO was less.…”
Section: Mechanical Properties Of the Scaffoldsmentioning
confidence: 99%
See 2 more Smart Citations